Pengembangan Modul Matematika Bernuansa Keislaman melalui Metode Scaffolding - Fitri Mulianda; Dian Anggraini (Universitas PGRI Adi Buana Surabaya, 2021)
The purpose of this research is in order to know the development, appropriateness, attractiveness and effectiveness of product developed in Al-Kautsar Bandar Lampung senior high school and MAN 2 Bandar Lampung. The procedure used is resert and development with research method and the 4-D development initiated by Thiagarajan. The data collection instrument conducted by spreading appropriateness questionnaires to the subject expert, media expert, religion expert, and education practitioner, deployment of appropriateness questionnaires to students in small scale trial and big scale trial and giving pre post test in effectiveness trial using N-Gain calculation. Obtained effectiveness result in the amount of 3,6 from subject expert, 3,5 from media expert, and 3,7 from religion expert, then its average is 3,6. It gets â€œvery decent barometerâ€. The studentsâ€™ response showed that the module is very interesting with average 3,47 from both schools with â€œvery decent criteriaâ€ on small scale trial and 3,3 with â€œvery decent criteriaâ€ on big scale trial. The result of effectiveness trial got 0,77 at SMA Al-Kautsar Bandar Lampung and 0,72 at MAN 2 Bandar Lampung. Based on Gain score range that is , so mathematics module framed in nuance of Islam through scaffolding on aljabar function limit subject is categorized with high classification